Transient imine as a directing group for the Pd-catalyzed anomeric C(sp3)–H arylation of 3-aminosugars. Issue 17 (8th February 2023) - Ghouilem, Juba; Bazzi, Sokna; Grimblat, Nicolas; Retailleau, Pascal; Gandon, Vincent; Messaoudi, Samir
Abstract : The first example of Pd(ii )-catalyzed anomeric C(sp 3 )–H arylation of 3-aminosugars by using a transient directing group approach is reported. The free amine was then exploited in a CuAAC reaction to access to a variety of C3-triazolo C -glycosides in good yields. Abstract : The first example of Pd(ii )-catalyzed anomeric arylation of 3-aminosugars is reported by using an L, X-type transient directing group (TDG) approach combined with an external 2-pyridone ligand. The released free amine was in situ transformed into an azide function, which was then exploited in a CuAAC to increase the molecular complexity and prepare a variety of complex substituted C3-triazolo C -glycosides in good yields.